Farming Daily Activities Sebagai Upaya Terapi Dan Edukasi Mantan Odgj di Kabupaten Madiun - Erliana Sari, Novita; Sunaryantiningsih, Ina; Maruti, Endang Sri; Nila Andriani, Dwi; Susanti, Lisa (Politeknik Penerbangan Indonesia Curug, 2022)
The purpose of this program is to assist ODGJ in doing farming daily activities as a therapeutic and educational effort. This activity was carried out in Doho Village, Dolopo District, Madiun Regency from March 2021 to September 2021. The target of this activity is Ex-ODGJ in Doho Village, Dolopo District, Madiun Regency, which has 11 people and has been declared stable so they can communicate and carry out their activities well. Based on the results of the activity, it can be concluded that the evaluation of the results of the therapeutic goals of farming daily activities for the eleven ODGJs in Doho Village, Madiun Regency, appears to have had many changes in both mental and spiritual development. Environmental conditions, as well as the involvement of family members in the therapy process are needed, compared to ODGJ who are not yet stable. This community service program was declared quite successful because it had: (1) fostered a sense of responsibility in ex-ODGJ; (2) Ex-ODGJ can have better physical and mental health because they have daily routines; and (3) ODGJ are able to generate their own income.